Microbial community-level regulation explains soil carbon responses to long-term litter manipulations - Katerina Georgiou (Nature Portfolio, 2017)
Microbial models of soil organic carbon feed into Earth System Models, but many exhibit unrealistic oscillatory behaviour. Here, the authors propose a density-dependent formulation of microbial turnover that improves microbial models, with large implications for global carbon-concentration feedbacks.